Factors affecting the adoption of drones in the food supply chain - Undre, Haaliema Bibi; Jokonya, Osden (Frontiers in Sustainable Food Systems, 2024)
The fourth industrial revolution's digital transformation has profoundly altered how we view the food supply chain. The technological advancements associated with the fourth industrial revolution (4IR) have witnessed an upsurge in emerging technologies adoption such as drones in the food supply chain. However, research on the factors affecting the adoption of drones in the food supply chain is limited. This study therefore addresses the research gap. The study's main objective is to explore factors affecting the adoption of drones in the food supply chain. The study conducted a systematic literature review of peer-reviewed articles. This quantitative study adopted the Technology-Organisational-Environmental (TOE) framework as the theoretical lens to explore the factors influencing drone adoption. The study indicates that technological factors (cost, relative advantage, and perceived usefulness), organisational factors (strategic objectives), and environmental factors (market structure) affect the adoption of drones in the food supply chain. Despite the study's limitations, such as secondary data rather than empirical data, the study contributes to the body of knowledge on the factors influencing the adoption of drones in the food supply chain.